Chronic stress and its relationship with increased food consumption and the risk of obesity - Kępczyk, Martyna; Kwaśniewska, Oliwia; Misiak, Jakub; Urbaś, Michał; Ojdana, Miłosz; Demianenko, Yehor; Czekaj, Oliwia; Kościołek, Aleksandra; Kościołek, Dawid; Surowiecka, Kaja (Journal of Education, Health and Sport, 2024)
INTRODUCTION AND AIM OF WORK Stress often accompanies daily functioning. This mechanism is activated by the body in response to external factors to effectively cope with challenges. With prolonged exposure, stress significantly impairs physiological functions, including impacting body weight. MATERIALS AND METHODS The aim of the study is to understand the impact of chronic stress on changes in dietary habits and body weight. For this purpose, a custom survey was created to investigate the correlation between stress and other factors. It was distributed using social media (Telegram) in the first half of August 2023 among the population of Ukraine. RESULTS The survey was completed by 110 individuals, with the majority being males, accounting for 67 participants (61%). The participants had an average age of 28 years with a standard deviation of 7.12. Among the responses, the most common frequency of experiencing stress was once every two weeks, with 41 answers (37.27% of participants). A majority of the respondents declared having a normal body weight (55.45%). In our study, we demonstrated a correlation between stress and unhealthy eating habits (rho-Spearman p=0.0002, r=0.34), as well as a lower frequency of stress among individuals taking antidepressant medication (p=0.012). However, we did not establish a connection with abnormal body weight (p>0.05), physical activity (p>0.05), or healthy eating (p>0.05). CONCLUSIONS The obtained results suggest that stress may trigger a response in the form of overeating. The reduction in the frequency of stress is also influenced by the use of medications. The findings may indicate a strong association between diet and the experience of stress.